2014
DOI: 10.4161/epi.29499
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex methylation specific PCR suitable for (early) detection of non-small cell lung cancer

Abstract: Lung cancer is a worldwide health problem and a leading cause of cancer-related deaths. Silencing of potential tumor suppressor genes (TSGs) by aberrant promoter methylation is an early event in the initiation and development of cancer. Thus, methylated cancer type-specific TSGs in DNA can serve as useful biomarkers for early cancer detection. We have now developed a "Multiplex Methylation Specific PCR" (MMSP) assay for analysis of the methylation status of multiple potential TSGs by a single PCR reaction. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 72 publications
1
19
1
Order By: Relevance
“…Therefore, our data provide evidence suggesting that HOXA9 is controlled by miR‐196b in NSCLC cells. Collectively, these data strongly suggest that HOXA9 expression in lung cancer tissues and cancer cell lines is controlled by miRNAs as well as by the methylation of the promoter, which is another form of epigenetic modification .…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, our data provide evidence suggesting that HOXA9 is controlled by miR‐196b in NSCLC cells. Collectively, these data strongly suggest that HOXA9 expression in lung cancer tissues and cancer cell lines is controlled by miRNAs as well as by the methylation of the promoter, which is another form of epigenetic modification .…”
Section: Discussionmentioning
confidence: 80%
“…Nowadays, a number of potential biomarkers have been reported, but very few have reached clinical standards to be an efficient index due to small study sizes and lack of assay optimization 22,23 . The aberrant of DLEC1 methylation had been reported in several cancers, such as prostate cancer 24 , gastric cancer 25 , and lung cancer 18 .…”
Section: Discussionmentioning
confidence: 95%
“…The modified DNA was amplified using real-time quantitative methylation-specific PCR (QMSP) as described by Nawaz et al 12 The target genes included CDH13, WT1, CDKN2A, HOXA9, PITX2, CALCA, RASSF1A, and DLEC1. The relative methylation level of the target genes was determined with β-actin as a reference gene.…”
Section: Real-time Quantitative Methylation-specific Polymerase Chainmentioning
confidence: 99%
“…One study found that the combined detection of multigene methylation can increase the sensitivity to 93%, but the specificity is decreased. 12 Even so, the concentration and integrity of free DNA in patients with cancer are higher than in healthy subjects, and detecting the methylation of lung cancer-associated genes by extracting free DNA in plasma is the trend in the early diagnosis of lung cancer in recent years.…”
Section: Introductionmentioning
confidence: 99%